ISOTOPIC EVIDENCE FOR TRAPPED FISSIOGENIC REE AND NUCLEOGENIC PU IN APATITE AND PB EVOLUTION AT THE OKLO NATURAL REACTOR - Horie K.; Hidaka H.; Gauthier-Lafaye F. (My University, 2004)
A part of the boundary layer of reactor zone 10 at the Oklo natural reactor shows a unique petrologic texture, which contains high-grade uraninite and massive apatite concretions. In order to study distribution behavior of fission products around the boundary between the reactor zone and the wall rock and to clarify the relation of migration mechanisms of fission products with geochemical factors, in-situ isotopic analyses of Nd, Sm, Gd, Pb and U in uraninite and apatite from the sample were performed by Sensitive High Resolution Ion Microprobe (SHRIMP). Sm and Gd isotopic ratios of uraninite and apatite show evidence of neutron irradiation with fluence between 4.4–6.8×1019 n/cm2. Judging from the isotopic anomalies of Nd and U, the apatite coexisting with the uraninite plays an important role in trapping fissiogenic LREE and nucleogenic 239Pu into the structure. Systematic Pb isotopic data from apatite, uraninite, galena and minium suggest the following chronological interpretations. 1.The apatite formed 1.92±0.01 Ga ago and trapped fissiogenic light REE and nucleogenic 239Pu that migrated from the reactor during the criticality.2.The uraninite around the boundary between reactor and sandstone dissolved once 1.1∼1.2 Ga ago.3.Galena grains were formed by U-Pb mobilization in association with the intrusion of dolerite dyke 0.45∼0.83 Ga ago.4.Minium was derived from recent dissolution of galena under locally oxidizing conditions.